ANALYSIS OF THE EFFECT OF AGING TIME ON AMORPHOUS PHASE NANOSILICA FROM PARANGLOE IGNEOUS ROCKS USING THE SOL-GEL METHOD - Rismawati Rismawati; Ahmad Fudhail Majid; Suriati Eka Putri (Jurusan Kimia FMIPA Universitas Lampung, 2024)
In this research, an analysis of the effect of aging time on amorphous phase nanosilica from Parangloeigneous rock was conducted using the sol-gel method. The research samples were taken from aroundthe Parangloe waterfall in Gowa regency, South Sulawesi province. The research stages includedsample preparation, nanosilica synthesis using the sol-gel method, and synthesis resultscharacterization. Characterization was performed using XRF, XRD, SEM-EDX, and PSA. XRF datashowed that the silica content was 53.62% in the form of white powder, and after synthesis, itdecreased to 12.38%. SEM-EDX testing results showed small agglomerated spheres with an EDX of4.52%. A 3-hour aging time variation resulted in an amorphous phase, making 3 hours the optimumtime for amorphous phase nanosilica formation with the highest peak intensity at 2Î¸=25.42 ° and aparticle size of 170.8 nm.